The One-Kilobase DNA Fragment Upstream of the ardC Actin Gene of Physarum polycephalum Is Both a Replicator and a Promoter - Pierron, Gérard (American Society for Microbiology, 1999)
The 1-kb DNA fragment upstream of the ardC actin gene of Physarum polycephalum promotes the transcription of a reporter gene either in a transient-plasmid assay or as an integrated copy in an ectopic position, defining this region as the transcriptional promoter of the ardC gene (PardC). Since we mapped an origin of replication activated at the onset of S phase within this same fragment, we examined the pattern of replication of a cassette containing the PardC promoter and the hygromycin phosphotransferase gene, hph, integrated into two different chromosomal sites. In both cases, we show by two-dimensional agarose gel electrophoresis that an efficient, early activated origin coincides with the ectopic PardC fragment. One of the integration sites was a normally late-replicating region. The presence of the ectopic origin converted this late-replicating domain into an early-replicating domain in which replication forks propagate with kinetics indistinguishable from those of the native PardC replicon. This is the first demonstration that initiation sites for DNA replication in Physarum correspond to cis-acting replicator sequences. This work also confirms the close proximity of a replication origin and a promoter, with both functions being located within the 1-kb proximal region of the ardC actin gene. A more precise location of the replication origin with respect to the transcriptional promoter must await the development of a functional autonomously replicating sequence assay in Physarum.